The Qualitative Researcher's Evolving Role: Instrument, Ethical Compass, and Reflexive Agent in Contemporary Inquiry (Surkhet Journal, 2025)
Qualitative research, interpretive in nature, positions the researcher as the central instrument for data collection and meaning interpretation, valuing subjectivity for knowledge co-construction. This paper critically examines the qualitative researcher’s role, emphasizing how reflexivity, positionality, and ethical conduct enhance trustworthiness and rigor. Using a conceptual and literature-based analysis guided by APA JARS-Qual (Levitt et al., 2018), the study synthesizes insights from foundational literature, empirical case studies, and best practices. Key practices reviewed include reflexive journals, positionality statements, member checking, and ethical training. Findings highlight that continuous critical self-reflection and ethical engagement are crucial for research rigor. By embracing subjectivity through structured reflexive practices, researchers transform potential bias into a methodological strength, deepening authenticity, contextual relevance, participant trust, and process transparency. Integrating reflexivity and ethical sensitivity is thus indispensable for credible, meaningful qualitative insights into complex social and health phenomena.